PENGEMBANGAN VIDEO PEMBELAJARAN VIDEOSCRIBE BERBASIS LITERASI SAINS DI SEKOLAH DASAR - Pipit Pitriyani; Aan Subhan Pamungkas; Trian Pamungkas Alamsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Scientific literacy is one of the skills that should be mastered in the 21st century. This scientific literacy can be implemented though the learning media. The purpose of this study was to develop a learning video by using a science-based Videoscribe application. The model of development in this study was the five-step ADDIE model of refinement analysis, design, development, implementation and evaluation. Based on the validation from language, material and media experts, the average percentage of the learning videos was 89.7% with